The dentobiome and the minimum intervention in dentistry - Aguilar-Gálvez, Denisse (2022)
All of us who observe the chilling figures of children with dental caries on a daily basis and more recently the more frequent presence of enamel alterations and among them incisor molar hypomineralization, we begin to think what really happens with that tissue considered the strongest of the human body; however, it bows down to an acid attack resulting from bacterial metabolism and the question arises: Could it be that the tooth is already born with a predisposition to develop certain microorganisms? This comprehensive review of the literature, summarizing the authors' perspectives; aims to explore the knowledge about the biome and apply it to the dental organ and make available the definition of dentobiome, as an appropriate term for dental flora. Starting from this knowledge, apply it to better understand today the execution of the philosophy of minimal intervention and the development of materials that must be biocompatible with the dental structure but must also prevent dysbiosis and establish homeostasis in the tooth.